PANCREATIC FIBROSIS AND ITS RELATION WITH POST PANCREATICODUODENECTOMY PANCREATIC FISTULA (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Pancreaticoduodenectomy (Whipple's Procedure and its variants) is the treatment of choice for malignant diseases of periampullary region. Postoperative Pancreatic Fistula (POPF) is the most dreaded complication and contributes substantially to the failure rate. Data regarding the relation of pancreatic fibrosis to pancreatic fistula is limited in the literature.Methods: Patients undergoing Pancreaticoduodenectomy (PD) for malignant etiology were included in the study. POPF was graded according to the International Study Group of Pancreatic Surgery (ISGPS) grading system into 3 Grades (A- mild, B- moderate, C -severe). Pancreatic Fibrosis Scale was used for Classification of pancreatic fibrosis into three types.Results: During the study period 48 patients of periampullary malignancy treated by PD at NHLM Medical College, VS Hospital, Ahmedabad where enrolled. The factors which were significantly associated with POPF in our study were Pancreatic duct size, Pancreatic Fibrosis, Age, DM, low albumin level and intraoperative blood loss. Type 1 fibrosis was found in 14 patients out of which Grade A fistula was found in 3 patients, Grade B fistula in 5 patients and Grade C fistula in 3 patients. Type 2 fibrosis was found in 17 patients of which Grade A fistula was found in 8 patients, Grade B fistula in 1 patient and none of Type 2 fibrosis developed Grade C fistula. Type 3 fibrosis was found in 17 patients out of which only 2 patient developed Grade A fistula and no patient developed grade B or C fistula with clinical relevance. High Grade of pancreatic fibrosis was associated with lower risk of POPF (0.005) compared to Low Grade fibrosis (p value 0.0002)Conclusion: Pancreatic fibrosis correlates well with POPF. The pathological findings of High Grade pancreatic fibrosis has protective effect and is related to the lower rate of pancreatic fistula as compared to Low Grade pancreatic fibrosis.
Keywords: Pancreaticoduodenectomy; Pancreatic fistula (POPF); Pancreatic fibrosis